The evaluation of the inquiry-based learning in biology classes from the grammar school teachers’ and students’ point of view - Radvanová, Sabina; Čížková, Věra; Martínková, Patrícia (Scientia in educatione, 2019)
The aim of the research was to design, verify and reflect upon the suggested inquiry-based activities in a real upper-secondary biology class settings, considering both the students’ and the teachers’ point of view. Firstly, a set of questionnaires for students as well as for teachers and worksheets for students were created. The obtained data were analysed quantitatively, while the students’ responses in the worksheets were analysed qualitatively. The results indicate that teachers make only sporadic use of inquiry-based learning (IBL). They most commonly incorporate some components of the IBL into practical exercises, practising lower levels of research with their students. Teachers considered the suggested inquiry-based activities more interesting than the students did. The students, on the other hand, viewed them as more demanding. Both groups of respondents considered them beneficial, although not always fully comprehensible. Furthermore, both students and teachers indicated they would welcome more leading information which would enable them to finish the assigned activities successfully. The students who stated their subjective interest in biology were much more appreciative of how intriguing, challenging, comprehensible and beneficial the activities were, as opposed to those students who were ostensibly not interested in biology. On the other hand, there was no difference in the perception of the above mentioned categories if we use the students’ gender as a criterion. Both the teachers and students generally expressed their belief that students should look up the information by themselves in biology classes rather than being presented with complete facts.